The leadership behavior of the physical education and sports teacher and its relationship to the level of creative thinking among secondary school students - بشيري بن عطية (sports creativity, 2025)
This study aims to identify the distinctive leadership behavior of physical education teachers and the level of creative thinking among secondary school students, and to explore the relationship between the two. The researcher posed the following questions: 1. What is the distinctive leadership behavior of physical education teachers? 2. What is the level of creative thinking among secondary school students? 3. Is there a correlation between the dominant leadership behavior of physical education teachers and the level of creative thinking among secondary school students?